Lamellar Keratoplasty as a Method of Treatment Patients with Neurotrophic Keratopathy II and III Stages Outcome - M. Ezugbaya; I. A. Riks; S. V. Trufanov; S. Yu. Astakhov; S. S. Papanyan; L. K. Anikina; R. Boutaba; V. V. Gryaznova (Oftalʹmologiâ, 2022)
Neurotrophic keratopathy (NTK) is an orphan, polyetiological disease that has recently been identified more frequently. Drug-resistant stages of NTC often require urgent surgical treatment. Subsequently, such patients need to be done keratoplasty, the consequences may be unsatisfactory in the presence of a significant impairment of innervation.Purpose: to evaluate the effectiveness of lamellar anterior keratoplasty in patients with the outcome of stage II and III NTK.Material and methods. The study included 22 patients (22 eyes) aged 21 to 88 years. All patients were divided into two main groups. The first group consisted of 12 patients with NTC as a result of damage to the main stem of n.trigeminus and its branch n.ophthalmicus, the second group consisted of 10 patients — NTC as a result of toxic damage due to uncontrolled instillation of local anesthetics and eyedrops with preservatives. Before inclusion in the study, 14 patients underwent autoconjunctivoplasty for the treatment of drug-resistant NTK stage II and III, 8 — corneoscleral flap coating. All patients underwent lamellar anterior keratoplasty. The following parameters were assessed: maximally corrected visual acuity (MCVA) and coefficient of corneal sensitivity reduction in an approximate way before and after 1 day, 2 weeks, 1 and 3 months after surgery; tear film break- up time (Norn test) and Schirmer’s I.Results. In the second group an increase in the level of BCVA and a clear graft was observed in all patients, while in the first group, the level of BCVA worsened, and the graft was with reduced transparency. Significant difference between the examined and the fellow eye in the compared groups according to the tear film break-up time test was not detected. In the first group statistically significant decrease of tear production according to the results of the Schirmer’s test was identified. A weak correlation was found between corneal sensitivity and BCVA after surgery in group II.Conclusion. We have demonstrated the high efficiency of automated layered anterior keratoplasty in the outcomes of advanced stages of NTK of toxic etiology. In patients with NTC outcome as a result of stem injury, surgical treatment led to a satisfactory cosmetic result, but visual acuity did not change significantly.